Optimal control of greenhouse cultivation - Straten, G. van [ (Gerrit van)] , 1946- (CRC Press/Taylor & Francis Group, 2011)
A reference on the development and advances in optimal greenhouse control. It focuses on model-based methods to achieve the best economical result. It discusses physical models of greenhouse climate and biological models of crop growth, as well as classical rule-based and multivariable feedback controllers